Kepemimpinan Wanita dalam Perspektif Syariah dan Sosiologi Hukum: Fenomena Pemilihan Gubernur Jawa Timur Tahun 2024 - Malaka, Zuman (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This research aims to analyze women's leadership from the perspective of sharia and legal sociology, as well as the opinions of several intellectual religious experts in the East Java region regarding women's leadership in the realm of politics and government, especially in the context of the 2024 East Java Governor Election. The research method used are, namely 1) Field study data obtained from interviews with several East Java intellectual religious experts as well as documentation such as recordings and photos needed to support research, 2) literature study using data from various literature such as the Al-Qur'an, hadith related to leadership women, as well as academic studies and statutory regulations such as the Election Law. The results of the research show that from a sharia perspective, there are differences in the textual interpretation of verses regarding political rights and women's leadership among Muslims. However, in the sharia view, leadership is not determined by the gender of the leader, but rather their piety and ability to carry out their responsibilities as leaders. Meanwhile, a legal sociology perspective shows that legal regulations in Indonesia encourage women's involvement in politics and government.